2021
DOI: 10.1111/ilr.12200
|View full text |Cite
|
Sign up to set email alerts
|

Internal migration, remittances and labour force participation in rural India: A gender perspective

Abstract: This article examines the impact of domestic remittances on the labour supply of men and women in recipient households in rural India. Applying the instrumental variable approach to data from the National Sample Survey, estimates indicate that remittances have a negative effect on the labour force participation of left‐behind household members. They do not seem to affect participation in regular salaried work but cause a decline in participation in casual wage work and unpaid family work, and an increase in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Prior studies have shown that disabled women face double discrimination in the labour market (Abubakar et al ., 2021; Orellano-Colón et al ., 2022). LFPR in disabled women is around one-tenth of the women are seeking work or working, given the already low and declining female labour force participation in general for India (Khan and Baruah, 2021) and across developing and emerging economies (Klasen et al ., 2021). Disabled women are perceived as weak, incapable, and dependent on others in their workplace (Varshney, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Prior studies have shown that disabled women face double discrimination in the labour market (Abubakar et al ., 2021; Orellano-Colón et al ., 2022). LFPR in disabled women is around one-tenth of the women are seeking work or working, given the already low and declining female labour force participation in general for India (Khan and Baruah, 2021) and across developing and emerging economies (Klasen et al ., 2021). Disabled women are perceived as weak, incapable, and dependent on others in their workplace (Varshney, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%